2021
DOI: 10.3390/ani11082440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recovery Quality Following Medetomidine versus Xylazine Balanced Isoflurane Anaesthesia in Horses: A Retrospective Analysis

Abstract: Medetomidine partial intravenous anaesthesia (PIVA) has not been compared to xylazine PIVA regarding quality of recovery. This clinical retrospective study compared recoveries following isoflurane anaesthesia balanced with medetomidine or xylazine. The following standard protocol was used: sedation with 7 µg·kg−1 medetomidine or 1.1 mg·kg−1 xylazine, anaesthesia induction with ketamine/diazepam, maintenance with isoflurane and 3.5 µg·kg−1·h−1 medetomidine or 0.7 mg·kg−1·h−1 xylazine, and sedation after anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The outcome was dichotomized as discharged/non-discharged. For those horses that underwent laparotomy, the following data were retrieved from surgery and the anesthetic records: anesthetic protocol, duration of anesthesia and surgery (minutes), time to standing (minutes) and recovery score [ 29 ], type of lesion (ischemic/non-ischemic), and occurrence of complications (if any/the type of complication).…”
Section: Methodsmentioning
confidence: 99%
“…The outcome was dichotomized as discharged/non-discharged. For those horses that underwent laparotomy, the following data were retrieved from surgery and the anesthetic records: anesthetic protocol, duration of anesthesia and surgery (minutes), time to standing (minutes) and recovery score [ 29 ], type of lesion (ischemic/non-ischemic), and occurrence of complications (if any/the type of complication).…”
Section: Methodsmentioning
confidence: 99%
“…However, to the authors' knowledge this has never been confirmed in a larger study population and in non-emergency cases. Conversely, use of salbutamol, a short acting β 2 -adrenoceptor agonist, used to treat hypoxaemia in anaesthetized horses, has been related to poorer recovery scores, and identified as a risk factor for catastrophic fractures or luxation's during recovery (Kälin et al 2021;Bennell et al 2022). Although salbutamol is used routinely for the treatment of hypoxaemia, neither of the two studies identified hypoxaemia itself as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…We must highlight that all horses in Group X received a bolus of xylazine once in the recovery room. Previous studies also emphasize the need for this measure [53,54] to improve recovery scores from general anesthesia during elective surgery. In all cases, recoveries were unassisted since no consensus was found in the literature concerning this aspect [55][56][57].…”
Section: Discussionmentioning
confidence: 99%